LEGALITY OF REGISTRATION FOR INTERNATIONAL RELIGIOUS MARRIAGE BASED ON COURT DECISIONS ACCORDING TO LAW AND REGULATIONS IN INDONESIA - Desimaliati Desimaliati (Universitas Lampung, 2022)
Law Number 1 of 1974 concerning Marriage (Marriage Law) as a guideline for norms (verwijzing) does not recognize interfaith marriages, but the Marriage Law itself provides a legal loophole in legalizing interfaith marriages. Many applications for interfaith marriage licenses that have been granted through Court Decisions and have been successfully registered at the Population and Civil Registry Office, are declared valid along with all their legal consequences in state administration and are legally binding on civil law. The purpose of this research is to explain application of legal theory and identify laws and regulations that form the legal basis for judges considerations in ratifying applications for registration of interfaith marriages through Court Decisions. The writing of this article uses normative legal research method. Data processing and library research using primary, secondary and tertiary legal sources. The results showed that the ratification of interfaith marriages through a Court Decision was born from another interpretation of Article 66 of the Marriage Law which was interpreted by the method of applying the principle of conflict of norms using the principle of legal logic (rechtslogische prinzipien) or presumption of rules (vermutungsregeln), so that the Marriage Law seems to have multiple interpretations. There are several other laws and regulations that underline the legalization of the registration of interfaith marriages in Indonesia. There are two views on the basis of the legal considerations of the Panel of Judges in accepting, examining and deciding cases of interfaith marriage applications through Court Decisions. To ensure legal protection and certainty for the parties and children born in a marriage, marriages need to be administratively registered in the state even though each marriages consist of different religions.